Perumahan Keluarga Muda Perkotaan: Kajian dan Perumusan Model Arsitektur - Siregar, Mohammad Jehansyah (Jurnal Aspirasi, 2017)
Attention on psychology of family development factor is not much considered yet in the provision of urban housing with regard to its natural relation between human and their housing. This paper describes a housing need assessment that is essential for the life of urban young family. This analysis creates a housing architectural model based on architectural design methodology, where characteristics in stages of family development cycle become the source of inspiration in the formulation of design principles of urban young family housing model. As the result of this analysis, housing model for urban young family describes houses that provide separated units in form of urban rental housing. The houses are small, compact and flexible units within a safe neigborhood and equipped with facilities that have attention on housing need of young families and become the place for interaction between mothers and children. As a model for urban housing design, output of this architectural research is potential for further exploration to develop a basic housing design prototype for young family in urban Indonesia.Faktor psikologi perkembangan keluarga dalam penyediaan perumahan di perkotaan yang didasarkan pada hubungan alami antara manusia dan huniannya masih belum cukup diperhatikan. Makalah ini memaparkan sebuah hasil kajian kebutuhan perumahan (housing need) yang sangat penting untuk kehidupan keluarga muda di perkotaan. Kajian ini menghasilkan model arsitektur perumahan berdasarkan metodologi perancangan arsitektur. Ciri-ciri kehidupan dalam tahap-tahap siklus perkembangan keluarga menjadi sumber inspirasi untuk merumuskan prinsip-prinsip perancangan perumahan untuk keluarga muda perkotaan. Model perumahan untuk keluarga muda perkotaan yang dihasilkan dari kajian ini memberikan gambaran perumahan sebagai tempat tinggal yang terpisah, dalam bentuk rumah sewa perkotaan. Model perumahan ini berbentuk unit-unit hunian yang kecil, kompak dan fleksibel, di lingkungan yang aman dari bahaya dan dilengkapi dengan fasilitas yang memperhatikan kebutuhan hunian pasangan muda, serta menjadi wadah yang optimal untuk interaksi ibu dan anak. Sebagai sebuah model umum untuk perancangan perumahan perkotaan, hasil penelitian arsitektur ini dapat dilanjutkan untuk membuat prototipe dasar perancangan perumahan keluarga muda di kawasan perkotaan di Indonesia.